Open Access

Some identities of higher-order Bernoulli, Euler, and Hermite polynomials arising from umbral calculus

  • Dae San Kim1,
  • Taekyun Kim2Email author,
  • Dmitry V Dolgy3 and
  • Seog-Hoon Rim4
Journal of Inequalities and Applications20132013:211

https://doi.org/10.1186/1029-242X-2013-211

Received: 3 January 2013

Accepted: 12 April 2013

Published: 26 April 2013

Abstract

In this paper, we study umbral calculus to have alternative ways of obtaining our results. That is, we derive some interesting identities of the higher-order Bernoulli, Euler, and Hermite polynomials arising from umbral calculus to have alternative ways.

MSC:05A10, 05A19.

Keywords

Bernoulli polynomialEuler polynomialAbel polynomial

1 Introduction

As is well known, the Hermite polynomials are defined by the generating function to be
e 2 x t t 2 = e H ( x ) t = n = 0 H n ( x ) t n n ! ,
(1.1)
with the usual convention about replacing H n ( x ) by H n ( x ) (see [1, 2]). In the special case, x = 0 , H n ( 0 ) = H n are called the nth Hermite numbers. The Bernoulli polynomials of order r are given by the generating function to be
( t e t 1 ) r e x t = n = 0 B n ( r ) ( x ) t n n ! ( r R ) .
(1.2)
From (1.2), the n th Bernoulli numbers of order r are defined by B n ( r ) ( 0 ) = B n ( r ) (see [116]). The higher-order Euler polynomials are also defined by the generating function to be
( 2 e t + 1 ) r e x t = n = 0 E n ( r ) ( x ) t n n ! ( r R ) ,
(1.3)

and E n ( r ) ( 0 ) = E n ( r ) are called the nth Euler numbers of order r (see [116]).

The first Stirling number is given by
( x ) n = x ( x 1 ) ( x n + 1 ) = l = 0 n S 1 ( n , k ) x l ( see [8, 13] ) ,
(1.4)
and the second Stirling number is defined by the generating function to be
( e t 1 ) n = n ! l = n S 2 ( l , n ) t l l ! ( see [8, 10, 13] ) .
(1.5)
For λ ( 1 ) C , the Frobenius-Euler polynomials are given by
( 1 λ e t λ ) r e x t = n = 0 H n ( r ) ( x | λ ) t n n ! ( r R ) ( see [3, 7] ) .
(1.6)

In the special case, x = 0 , H n ( r ) ( 0 | λ ) = H n ( r ) ( λ ) are called the nth Frobenius-Euler numbers of order r.

Let be the set of all formal power series in the variable t over with
F = { f ( t ) = k = 0 a k k ! t k | a k C } .
Let us assume that is the algebra of polynomials in the variable x over and that P is the vector space of all linear functionals on . L | p ( x ) denotes the action of the linear functional L on a polynomial p ( x ) , and we remind that the vector space structure on P is defined by
L + M | p ( x ) = L | p ( x ) + M | p ( x ) , c L | p ( x ) = c L | p ( x ) ,

where c is a complex constant (see [8, 10, 13]).

The formal power series f ( t ) = k = 0 a k k ! t k F defines a linear functional on by setting
f ( t ) | x n = a n for all  n 0 ( see [8, 10, 13] ) .
(1.7)
Then, by (1.7), we get
t k | x n = n ! δ n , k ( n , k 0 ) ,
(1.8)

where δ n , k is the Kronecker symbol (see [8, 10, 13]).

Let f L ( t ) = k = 0 L | x k k ! t k (see [13]). For f L ( t ) = k = 0 L | x k k ! t k , we have f L ( t ) | x n = L | x n . The map L f L ( t ) is a vector space isomorphism from P onto . Henceforth, will be thought of as both a formal power series and a linear functional. We will call the umbral algebra. The umbral calculus is the study of umbral algebra (see [8, 10, 13]).

The order o ( f ( t ) ) of the non-zero power series f ( t ) is the smallest integer k for which the coefficient of t k does not vanish. A series f ( t ) having o ( f ( t ) ) = 1 is called a delta series, and a series f ( t ) having o ( f ( t ) ) = 0 is called an invertible series. Let f ( t ) be a delta series and let g ( t ) be an invertible series. Then there exists a unique sequence S n ( x ) of polynomials such that g ( t ) f ( t ) k | S n ( x ) = n ! δ n , k , where n , k 0 . The sequence S n ( x ) is called a Sheffer sequence for ( g ( t ) , f ( t ) ) , which is denoted by S n ( x ) ( g ( t ) , f ( t ) ) . By (1.7) and (1.8), we see that e y t | p ( x ) = p ( y ) . For f ( t ) F and p ( x ) P , we have
f ( t ) = k = 0 f ( t ) | x k k ! t k , p ( x ) = k = 0 t k | p ( x ) k ! x k ,
(1.9)
and, by (1.9), we get
p ( k ) ( 0 ) = t k | p ( x ) , 1 | p ( k ) ( x ) = p ( k ) ( 0 ) .
(1.10)
Thus, from (1.10), we have
t k p ( x ) = p ( k ) ( x ) = d k p ( x ) d x k .
(1.11)

In [8, 10, 13], we note that f ( t ) g ( t ) | p ( x ) = g ( t ) | f ( t ) p ( x ) .

For S n ( x ) ( g ( t ) , f ( t ) ) , we have
1 g ( f ¯ ( t ) ) e y f ¯ ( t ) = k = 0 S k ( y ) k ! t k for all  y C ,
(1.12)
where f ¯ ( t ) is the compositional inverse of f ( t ) . For S n ( x ) ( g ( t ) , f ( t ) ) and r n ( x ) = ( h ( t ) , l ( t ) ) , let us assume that
S n ( x ) = k = 0 n C n , k r k ( x ) ( see [8, 10, 13] ) .
(1.13)
Then we have
C n , k = 1 k ! h ( f ¯ ( t ) ) g ( f ¯ ( t ) ) l ( f ¯ ( t ) ) k | x n ( see [13] ) .
(1.14)

Equations (1.13) and (1.14) are called the alternative ways of Sheffer sequences.

In this paper, we study umbral calculus to have alternative ways of obtaining our results. That is, we derive some interesting identities of the higher-order Bernoulli, Euler, and Hermite polynomials arising from umbral calculus to have alternative ways.

2 Some identities of higher-order Bernoulli, Euler, and Hermite polynomials

In this section, we use umbral calculus to have alternative ways of obtaining our results. Let us consider the following Sheffer sequences:
E n ( r ) ( x ) ( ( e t + 1 2 ) r , t ) , H n ( x ) ( e 1 4 t 2 , t 2 ) .
(2.1)
Then, by (1.13), we assume that
E n ( r ) ( x ) = k = 0 n C n , k H k ( x ) .
(2.2)
From (1.14) and (2.2), we have
C n , k = 1 k ! e 1 4 t 2 ( e t + 1 2 ) r ( t 2 ) k | x n = 1 k ! 2 k ( 2 e t + 1 ) r e 1 4 t 2 | t k x n = 2 k ( n k ) ( 2 e t + 1 ) r | e 1 4 t 2 x n k = 2 k ( n k ) ( 2 e t + 1 ) r | l = 0 [ n k 2 ] 1 4 l l ! t 2 l x n k = 2 k ( n k ) l = 0 [ n k 2 ] 1 2 2 l l ! ( n k ) 2 l 1 | ( 2 e t + 1 ) r x n k 2 l = 2 k ( n k ) l = 0 [ n k 2 ] 1 2 2 l l ! ( n k ) 2 l E n k 2 l ( r ) = n ! 0 l n k , l : even E n k l ( r ) ( l 2 ) ! 2 k + l k ! ( n k l ) ! .
(2.3)

Therefore, by (2.2) and (2.3), we obtain the following theorem.

Theorem 2.1 For n 0 , we have
E n ( r ) ( x ) = n ! k = 0 n { 0 l n k , l : even E n k l ( r ) k ! ( n k l ) ! 2 k + l ( l 2 ) ! } H k ( x ) .
Let us consider the following two Sheffer sequences:
B n ( r ) ( x ) ( ( e t 1 t ) r , t ) , H n ( x ) ( e 1 4 t 2 , t 2 ) .
(2.4)
Let us assume that
B n ( r ) ( x ) = k = 0 n C n , k H k ( x ) .
(2.5)
By (1.14) and (2.4), we get
C n , k = 1 k ! e 1 4 t 2 ( e t 1 t ) r ( t 2 ) k | x n = 2 k ( n k ) ( t e t 1 ) r | l = 0 ( 1 4 ) l 1 l ! t 2 l x n k = 2 k ( n k ) l = 0 [ n k 2 ] 1 l ! 4 l ( n k ) 2 l ( t e t 1 ) r | x n k 2 l = 2 k ( n k ) l = 0 [ n k 2 ] ( n k ) ! l ! 2 2 l ( n k 2 l ) ! 1 | ( t e t 1 ) r x n k 2 l = 2 k ( n k ) l = 0 [ n k 2 ] ( n k ) ! l ! 2 2 l ( n k 2 l ) ! B n k 2 l ( r ) = n ! 0 l n k , l : even B n k l ( r ) k ! ( n k l ) ! 2 k + l ( l 2 ) ! .
(2.6)

Therefore, by (2.5) and (2.6), we obtain the following theorem.

Theorem 2.2 For n 0 , we have
B n ( r ) ( x ) = n ! k = 0 n { 0 l n k , l : even B n k l ( r ) k ! ( n k l ) ! 2 k + l ( l 2 ) ! } H k ( x ) .
Consider
H n ( r ) ( x | λ ) ( ( e t λ 1 λ ) r , t ) , H n ( x ) ( e 1 4 t 2 , t 2 ) .
(2.7)
Let us assume that
H n ( r ) ( x | λ ) = k = 0 n C n , k H k ( x ) .
(2.8)
By (1.14), we get
C n , k = 1 k ! e 1 4 t 2 ( e t λ 1 λ ) r ( t 2 ) k | x n = 1 k ! 2 k ( 1 λ e t λ ) r e 1 4 t 2 | t k x n = 2 k ( n k ) l = 0 [ n k 2 ] ( n k ) 2 l l ! 4 l 1 | ( 1 λ e t λ ) r x n k 2 l = n ! l = 0 [ n k 2 ] H n k 2 l ( r ) ( λ ) l ! 2 2 l + k ( n k 2 l ) ! k ! = n ! 0 l n k , l : even H n k l ( r ) ( λ ) ( l 2 ) ! 2 k + l ( n k l ) ! k ! .
(2.9)

Therefore, by (2.8) and (2.9), we obtain the following theorem.

Theorem 2.3 For n 0 , we have
H n ( r ) ( x | λ ) = n ! k = 0 n { 0 l n k , l : even H n k l ( r ) ( λ ) k ! ( n k l ) ! ( l 2 ) ! 2 k + l } H k ( x ) .
Let us assume that
H n ( x ) = k = 0 n C n , k E k ( r ) ( x ) .
(2.10)
From (1.14), (2.1), and (2.10), we have
C n , k = 1 k ! ( e 2 t + 1 2 ) r e 1 4 ( 2 t ) 2 ( 2 t ) k | x n = 1 k ! ( e t + 1 2 ) r e 1 4 t 2 t k | ( 2 x ) n = 1 k ! 2 n ( e t + 1 2 ) r e 1 4 t 2 | t k x n = 2 n ( n k ) ( e t + 1 2 ) r | l = 0 ( 1 ) l l ! 4 l t 2 l x n k = 2 n r ( n k ) l = 0 [ n k 2 ] ( 1 ) l l ! 2 2 l ( n k ) 2 l ( e t + 1 ) r | x n k 2 l = 1 2 r j = 0 r l = 0 [ n k 2 ] ( n k ) ( r j ) 2 k ( 1 ) l ( n k ) ! l ! ( n k 2 l ) ! ( 2 j ) n k 2 l .
(2.11)

Therefore, (2.10) and (2.11), we obtain the following theorem.

Theorem 2.4 For n 0 , we have
H n ( x ) = 1 2 r k = 0 n { j = 0 r l = 0 [ n k 2 ] ( n k ) ( r j ) 2 k ( 1 ) l ( n k ) ! ( 2 j ) n k 2 l l ! ( n k 2 l ) ! } E k ( r ) ( x ) .
Note that H n ( x ) ( e 1 4 t 2 , t 2 ) . Thus, we have
e 1 4 t 2 H n ( x ) ( 1 , t 2 ) , and ( 2 x ) n ( 1 , t 2 ) .
(2.12)
From (2.12), we have
e 1 4 t 2 H n ( x ) = ( 2 x ) n H n ( x ) = e 1 4 t 2 ( 2 x ) n .
(2.13)
By (2.11) and (2.13), we also see that
C n , k = 1 k ! ( e 2 t + 1 2 ) r e 1 4 ( 2 t ) 2 ( 2 t ) k | x n = 1 k ! ( e t + 1 2 ) r t k | e 1 4 t 2 ( 2 x ) n = 1 k ! 2 r ( e t + 1 ) r | t k H n ( x ) = 1 2 r ( n k ) 2 k j = 0 r ( r j ) H n k ( j ) .
(2.14)

Therefore, by (2.10) and (2.14), we obtain the following theorem.

Theorem 2.5 For n 0 , we have
H n ( x ) = 1 2 r k = 0 n ( n k ) 2 k [ j = 0 r ( r j ) H n k ( j ) ] E k ( r ) ( x ) .
Let us assume that
H n ( x ) = k = 0 n C n , k B k ( r ) ( x ) .
(2.15)
From (1.14), (2.4), and (2.15), we have
C n , k = 1 k ! ( e 2 t 1 2 t ) r e 1 4 ( 2 t ) 2 ( 2 t ) k | x n = 1 k ! ( e t 1 t ) r e 1 4 t 2 t k | ( 2 x ) n = 1 k ! ( e t 1 t ) r t k | e 1 4 t 2 ( 2 x ) n .
(2.16)
From (2.13) and (2.16), we have
C n , k = 1 k ! ( e t 1 t ) r t k | H n ( x ) .
(2.17)
For r > n , by (1.5) and (2.17), we get
C n , k = 1 k ! ( e t 1 ) k | ( e t 1 t ) r k H n ( x ) = 1 k ! ( e t 1 ) k | l = 0 n ( r k ) ! ( l + r k ) ! S 2 ( l + r k , r k ) t l H n ( x ) = 1 k ! l = 0 n ( r k ) ! ( l + r k ) ! S 2 ( l + r k , r k ) 2 l ( n ) l ( e t 1 ) k | H n l ( x ) = 1 k ! l = 0 n ( r k ) ! ( l + r k ) ! S 2 ( l + r k , r k ) 2 l n ! ( n l ) ! j = 0 k ( k j ) ( 1 ) k j H n l ( j ) = n ! j = 0 k l = 0 n ( r k ) ! S 2 ( l + r k , r k ) ( 1 ) k j ( k j ) 2 l H n l ( j ) ( l + r k ) ! k ! ( n l ) ! .
(2.18)

Therefore, by (2.15) and (2.18), we obtain the following theorem.

Theorem 2.6 For r > n 0 , we have
H n ( x ) = n ! k = 0 n { j = 0 k l = 0 n ( r k ) ! S 2 ( l + r k , r k ) ( 1 ) k j ( k j ) 2 l H n l ( j ) ( l + r k ) ! k ! ( n l ) ! } B k ( r ) ( x ) .
Let us assume that r n . For 0 k < r , by (2.18), we get
C n , k = n ! j = 0 k l = 0 n ( r k ) ! S 2 ( l + r k , r k ) ( 1 ) k j ( k j ) 2 l H n l ( j ) ( l + r k ) ! k ! ( n l ) ! .
(2.19)
For r k n , by (2.17), we get
C n , k = 1 k ! j = 0 r ( r j ) ( 1 ) r j e j t | D k r H n ( x ) = 2 k r n ! k ! ( n k + r ) ! j = 0 r ( r j ) ( 1 ) r j H n k + r ( j ) .
(2.20)

Therefore, by (2.15), (2.19), and (2.20), we obtain the following theorem.

Theorem 2.7 For n r , we have
H n ( x ) = n ! k = 0 r 1 { j = 0 k l = 0 n ( r k ) ! S 2 ( l + r k , r k ) ( 1 ) k j ( k j ) 2 l H n l ( j ) ( l + r k ) ! k ! ( n l ) ! } B k ( r ) ( x ) + n ! k = r n { j = 0 r ( 1 ) r j ( r j ) 2 k r H n k + r ( j ) k ! ( n k + r ) ! } B k ( r ) ( x ) .
Let us assume that
H n ( x ) = k = 0 n C n , k H k ( r ) ( x | λ ) .
(2.21)
Then, by (1.14), (2.7), and (2.21), we get
C n , k = 1 k ! ( e 2 t λ 1 λ ) r e 1 4 ( 2 t ) 2 ( 2 t ) k | x n = 1 k ! ( e t λ 1 λ ) r e 1 4 t 2 t k | ( 2 x ) n = 1 k ! ( e t λ 1 λ ) r t k | e 1 4 t 2 ( 2 x ) n .
(2.22)
By (2.13) and (2.22), we get
C n , k = 1 k ! ( e t λ 1 λ ) r t k | H n ( x ) = 1 k ! ( 1 λ ) r ( e t λ ) r | t k H n ( x ) = ( n k ) 2 k ( 1 λ ) r j = 0 r ( r j ) ( λ ) r j e j t | H n k ( x ) = ( n k ) 2 k ( 1 λ ) r j = 0 r ( r j ) ( λ ) r j H n k ( j ) .
(2.23)

Therefore, by (2.21) and (2.23), we obtain the following theorem.

Theorem 2.8 For n 0 , we have
H n ( x ) = 1 ( 1 λ ) r k = 0 n ( n k ) 2 k [ j = 0 r ( r j ) ( λ ) r j H n k ( j ) ] H k ( r ) ( x | λ ) .
Remark From (2.22), we have
C n , k = 1 k ! ( e t λ 1 λ ) r e 1 4 t 2 t k | ( 2 x ) n = 2 n k ! ( e t λ 1 λ ) r e 1 4 t 2 | t k x n = ( n ) k k ! 2 n l = 0 [ n k 2 ] ( 1 ) l l ! 4 l ( e t λ 1 λ ) r | t 2 l x n k = ( n k ) 2 n ( 1 λ ) r l = 0 [ n k 2 ] ( 1 ) l l ! 2 2 l ( n k ) 2 l ( e t λ ) r | x n k 2 l = 1 ( 1 λ ) r j = 0 r l = 0 [ n k 2 ] ( n k ) ( r j ) 2 k ( 1 ) l ( λ ) r j ( n k ) ! ( 2 j ) n k 2 l l ! ( n k 2 l ) ! .
(2.24)
Thus, by (2.21) and (2.24), we get
H n ( x ) = 1 ( 1 λ ) r k = 0 n { j = 0 r l = 0 [ n k 2 ] ( n k ) ( r j ) 2 k ( 1 ) l ( λ ) r j ( n k ) ! ( 2 j ) n k 2 l l ! ( n k 2 l ) ! } H k ( r ) ( x | λ ) .

Declarations

Acknowledgements

This paper is supported in part by the Research Grant of Kwangwoon University in 2013.

Authors’ Affiliations

(1)
Department of Mathematics, Sogang University
(2)
Department of Mathematics, Kwangwoon University
(3)
Hanrimwon, Kwangwoon University
(4)
Department of Mathematics Education, Kyungpook National University

References

  1. Kim DS, Kim T, Rim S-H, Lee S-H: Hermite polynomials and their applications associated with Bernoulli and Euler numbers. Discrete Dyn. Nat. Soc. 2012., 2012: Article ID 974632. doi:10.1155/2012/974632Google Scholar
  2. Kim T, Choi J, Kim YH, Ryoo CS: On q -Bernstein and q -Hermite polynomials. Proc. Jangjeon Math. Soc. 2011, 14(2):215–221.MathSciNetGoogle Scholar
  3. Araci S, Acikgoz M: A note on the Frobenius-Euler numbers and polynomials associated with Bernstein polynomials. Adv. Stud. Contemp. Math. 2012, 22(3):399–406.MathSciNetGoogle Scholar
  4. Araci S, Erdal D, Seo J: A study on the fermionic p -adic q -integral representation on Z p associated with weighted q -Bernstein and q -Genocchi polynomials. Abstr. Appl. Anal. 2011., 2011: Article ID 649248Google Scholar
  5. Bayad A: Modular properties of elliptic Bernoulli and Euler functions. Adv. Stud. Contemp. Math. 2010, 20(3):389–401.MathSciNetGoogle Scholar
  6. Can M, Cenkci M, Kurt V, Simsek Y: Twisted Dedekind type sums associated with Barnes’ type multiple Frobenius-Eulerl-functions. Adv. Stud. Contemp. Math. 2009, 18(2):135–160.MathSciNetGoogle Scholar
  7. Carlitz L: The product of two Eulerian polynomials. Math. Mag. 1963, 368: 37–41.View ArticleGoogle Scholar
  8. Dere R, Simsek Y: Applications of umbral algebra to some special polynomials. Adv. Stud. Contemp. Math. 2012, 22: 433–438.MathSciNetGoogle Scholar
  9. Ding D, Yang J: Some identities related to the Apostol-Euler and Apostol-Bernoulli polynomials. Adv. Stud. Contemp. Math. 2010, 20(1):7–21.MathSciNetGoogle Scholar
  10. Kim DS, Kim T: Some identities of Frobenius-Euler polynomials arising from umbral calculus. Adv. Differ. Equ. 2012., 2012: Article ID 196. doi:10.1186/1687–1847–2012–196Google Scholar
  11. Ozden H, Cangul IN, Simsek Y: Remarks on q -Bernoulli numbers associated with Daehee numbers. Adv. Stud. Contemp. Math. 2009, 18(1):41–48.MathSciNetGoogle Scholar
  12. Rim S-H, Joung J, Jin J-H, Lee S-J: A note on the weighted Carlitz’s type q -Euler numbers and q -Bernstein polynomials. Proc. Jangjeon Math. Soc. 2012, 15: 195–201.MathSciNetGoogle Scholar
  13. Roman S: The Umbral Calculus. Dover, New York; 2005.Google Scholar
  14. Ryoo C: Some relations between twisted q -Euler numbers and Bernstein polynomials. Adv. Stud. Contemp. Math. 2011, 21(2):217–223.MathSciNetGoogle Scholar
  15. Simsek Y: Special functions related to Dedekind-type DC-sums and their applications. Russ. J. Math. Phys. 2010, 17: 495–508. 10.1134/S1061920810040114MathSciNetView ArticleGoogle Scholar
  16. Simsek Y: Generating functions of the twisted Bernoulli numbers and polynomials associated with their interpolation functions. Adv. Stud. Contemp. Math. 2008, 16(2):251–278.MathSciNetGoogle Scholar

Copyright

© Kim et al.; licensee Springer 2013

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.